Pendampingan UMKM Tape Semen Bu Suwarti Dalam Pembuatan NIB & Branding Untuk Meningkatkan Daya Saing - Chrystia Aji Putra; Seftia Triwulan Dari; Audy Herlina Puspitasari; Reydiva Novia Hermawan; Salsabila Zahra Maulidina; Muhammad Adli Al Fawwaz (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Micro, Small and Medium Enterprises or MSMEs have an important role in the economy in Indonesia. Business legality that is officially recognized by the government, such as a Business Identification Number, is the main prerequisite for gaining consumer trust and access to various other business opportunities, including financing and partnerships. The aim of this activity is to provide assistance to Bu Suwarti Semen Tape MSMEs regarding NIB creation, starting from the registration process to NIB processing so that the business is recognized as legal by the government, and by developing branding for the Bu Suwarti Semen Tape product, it can increase the attractiveness and competitiveness of its products. on the market. The MSME assistance work program is carried out using several methods including surveys, observations, interviews and discussions, as well as mentoring. This assistance is carried out in two stages, namely assistance in creating a Business Identification Number which starts from the registration process to processing the NIB so that the legality of the business is recognized by the government. Next, the second stage is assistance with MSME branding through creating a visual identity which aims to increase the attractiveness and competitiveness of this tape product on the market.